Perspective of Public Policy Change the Change of Minimum Wage Policy in South Sulawesi: an Analysis of Advocacy Coalition Framework - Muhammad Rusdi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Changing of minimum wage policy option by the actors in 2006 is caused mainly by any change from internal aspects of policy subsystem directly, especially the change of secondary aspects of two advocacy coalition of minimum wage in South Sulawesi. This case mainly influenced from implementation the decentralization aspect where labors or group of labors have also any opportunity to involve in wage policy debate or in the forum of board of Provincial Waging. Furthermore, the Board of Manpower (Dinas Tenaga Kerja) of South Sulawesi Province which is identified as the policy broker has an important role to meet policy subsystem’s different strategies. As a result, conflict of minimum wage between labors and employers can reduce and they can act as a mediator to chooce the wage policy.Keywords: minimum wage, advocacy coalition framework